2014
DOI: 10.1155/2014/425856
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Students: What Teachers Have to Say

Abstract: In this exploratory qualitative study we examined teachers' perceptions of teacher behaviors that convey caring in upper elementary and middle school classrooms. Data collection included teacher interview, classroom observations, and teacher self-reflection. Major findings include specific caring behaviors perceived by teachers that are identified and described in four themes: (a) fostering a sense of belonging, (b) getting to know students personally, (c) supporting academic success, and (d) attending to phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…As the user, students can adjust their visual background light of their device and their room to reduce eye strain. However, as a facilitator, teachers should give breaks as proof of the teacher's understanding and evaluation toward students' condition (Garza et. al., 2014;Narinasamy, 2018).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…As the user, students can adjust their visual background light of their device and their room to reduce eye strain. However, as a facilitator, teachers should give breaks as proof of the teacher's understanding and evaluation toward students' condition (Garza et. al., 2014;Narinasamy, 2018).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In fact, research examining middle school students' perceptions of relationships with teachers indicated that acknowledgment of student success, emotional closeness, willingness to help, and high expectations were all noted as key elements in a high-quality student-teacher relationship (Alder, 2002;Guess & Bowling, 2014). Similarly, teachers of middle school students in one sample reported that providing praise to students within the context of supporting academic success is one component of teacher behavior that contributes to care and closeness with students (Garza et al, 2014). Murphy and Zlomke (2014) indicated that positive student-teacher interactions support students' social development and can improve their attitude toward school, thereby improving their attitude toward their teacher and classroom learning environment.…”
Section: Evidence Supporting Teacher Praise With Middle and High Schomentioning
confidence: 99%
“…Caring and nurturing characteristics: Caring can be viewed as fostering a sense of belonging, getting to know students personally, supporting academic success and attending to physiological needs (Garza et al 2014 :1).…”
Section: Resultsmentioning
confidence: 99%